PROFIL TEKSTUR, DAYA REHIDRASI, COOKING LOSS MIE KERING SUBSTITUSI PASTA LABU KUNING DAN PEWARNA ALAMI - Zulhaq Dahri Siqhny; Anisa Rachma Sari (Jurnal Agritechno, 2022)
Pumpkin, high carbohydrate local food potential to substitute for wheat. The substitution of pumpkin pasta and addition of natural dyes affected the texture properties and cooking quality dry noodles. The purpose was finding formulation of dry noodles with pumpkin pasta substitution and addition of natural dyes, analyze the characteristic of the texture properties and cooking quality of dry noodles. This study used one factor RAK, the ratio of wheat flour and pumpkin pasta with 6 levels, are: 100% wheat flour and 0% pumpkin pasta with or without addition of carrot juice, 90% wheat flour and 10% pumpkin pasta until 60% wheat flour and 40% pumpkin pasta with addition of carrot juice. Each groups was repeated 4 times. The observed parameters were hardness, cohesivenness, springiness, adhesion, gumminess, rehydration ability and cooking loss. The results showed the addition of pumpkin pasta didn’t affect the cohesiveness, adhesion, gumminess, and hardness, but affected the springiness, rehydration ability and cooking loss dry noodles. The substitution of 20% pumpkin pasta and the addition of carrot juice in the making of dry noodles is the best formulation because of low cooking loss value, high rehydration ability and have same texture properties as dry noodles from wheat flour.